Schizophrenia patients nursing - Petravičienė, Zita; Bartašiūnienė, Vida (Slauga. Mokslas ir praktika, 2020)
The lack of public knowledge about schizophrenia with sick persons, it is important to disclose, what are the needs for nursing care of these people.The object of – schizophrenia patients nursing.The aim – to analyze the schizophrenic patients care.The anonymous questionnaire form interviewed 24 nurses who work with patients with schizophrenia in Utena and Jasiuliškių social care homes. The questionnaire consisted of four blocks of questions. Questions based on the purpose and tasks of the study.The results showed that schizophrenia remission nurses help is most needed vital communication activity.The results showed that schizophrenia a disease exacerbation nurses help is most needed vital safe environment activity.Set the margins of the work as a nurse, working with patients suffering from schizophrenia, a disease remissions and exacerbation.Advice and knowledge about the disease, its impact on the sick, providing the patient‘s relatives are the main carers for cooperation with relatives of patients with schizophrenia principle.
Keywords: nursing needs; mental disorders; patient